Sierra Leone : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Sierra Leone during 1994-96. The disruption to agriculture at the start of the rebel war precipitated negative growth in 1991/92 and 1992/93. The relatively peaceful conditions that prevailed in 1993/94 brought a rebound in agriculture as well as in diamond mining activities. As a result, real GDP grew by an estimated 5 percent. The turnaround was cut short in 1994/95 with the escalation of rebel attacks and amid closure of rutile and bauxite mining operations.